Mexico : 2005 Article IV Consultation Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mexico. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that the economic recovery in Mexico that began in mid-2003 has continued in 2005, though at a slower pace. A broad-based expansion of economic activity in 2004, driven by a rebound of private consumption and private investment, took growth up to 4.4 percent. The fiscal accounts improved in 2004 on the strength of rising oil revenues and restraint of current expenditures, and the authorities achieved their target for the traditional deficit of 0.3 percent of GDP.